The Crucial Role of Prime Numbers in Cryptographic Techniques - Parameswaran.P (International Journal of Engineering and Management Research, 2020)
Prime numbers are at the heart of modern cryptographic techniques, forming the building blocks of secure data protection. This article explores the indispensable role that prime numbers play in cryptography, from their use in encryption and key generation to the foundation of secure digital communication. By understanding how prime numbers contribute to cryptographic security, we gain insight into the intricate mathematical principles that underpin the safeguarding of sensitive information.